Urinary System anomalies at birth - Menasinkai, Sharada B.; Chiniwar, Mahantappa A.; Saraswathi, G. (International Journal of Research in Medical Sciences, 2017)
Background: Congenital anomalies of urinary system are common and are found in 3-4% of population, and lethal urinary anomalies account for 10% of termination of pregnancy. Methods: A study was done to know the incidence of congenital anomalies at birth for the period of 4 months from May 99 - Sept 99 at Cheluvamba hospital attached to Mysore medical college. Congenital anomalies in the still births, live births and aborted fetuses >20 weeks were studied along with the case history and ultrasound reports. Aborted fetuses and still born babies were collected for autopsy after the consent of parents. These babies were fixed in 10% formalin and autopsy was done after fixing, and anomalies were noted. Results: Total births during study period were 3000. There were 61 babies with congenital anomalies and 6 babies had anomalies of urinary system. Among the urinary system anomalies 1 baby had bilateral renal agenesis, 1 baby had unilateral renal agenesis with anophthalmia (Fraser syndrome), 2 babies had Multicystic dysplastic kidney disease (MCDK) and 1 live baby had hydronephrosis due to obstruction at pelvi ureteric junction, and 1 live female baby had polycystic kidneys. Conclusion: Incidence of urinary system anomalies in the present study was 2 per 1000 births. U/S detection of urinary anomalies varies with period of gestation, amniotic fluid volume and visualisation of urinary bladder. Autopsy helps to detect renal agenesis.